Evolusi Ancaman Terorisme Pasca-ISIS : Tantangan Strategis Bagi Asia Tenggara - Aidil Aidil (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2025)
Following the fall of the ISIS caliphate in the Middle East, the threat of terrorism did not immediately disappear. On the contrary, the transformation of ISIS's strategy and patterns of ideological dissemination has opened a new chapter in the region's security dynamics, including in Southeast Asia. Indonesia and the Philippines have become two countries significantly impacted by the spread of ISIS-affiliated networks and ideology, both through direct attacks and digital propaganda. This study seeks to analyze how the evolution of the post-ISIS terrorist threat may influence the security policies of these two countries, as well as how national and regional strategic responses are formulated to confront this challenge. This research employs a qualitative approach with a literature study method, and utilizes traditional security and human security theories as its analytical framework. Preliminary findings indicate that the character of the post-ISIS threat tends to be decentralized, relying on individual radicalization and small cells. While Indonesia prioritizes a counter-radicalization and legal regulatory approach, the Philippines focuses more on large-scale military operations. This study affirms the importance of regional cooperation in strengthening security capacity, as well as the need for more adaptive strategies against the ever-evolving new forms of terrorist threats.